2012
DOI: 10.1007/s00330-012-2710-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reduced field of view in diffusion tensor imaging of the lumbar nerve roots at 3 T

Abstract: • Diffusion tensor 3-T MR imaging of lumbar nerve roots creates severe artefacts. • A reduced field of view drastically reduces artefacts, thereby improving image quality. • Good-quality tractography images can even be obtained with rFOV imaging. • rFOV DTI is better than fFOV DTI for clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 18 publications
2
36
2
Order By: Relevance
“…Except for one continued. article 7) (which showed low ADC), 9 articles [9][10][11]13,15,16,22,23,29) described high ADC in involved nerves and 5 articles demonstrated findings of ADC in healthy subjects 8,18,[24][25][26] . In an asymptomatic case, FA increased and ADC decreased following compression of the nerve root without injury 21) .…”
Section: Measurement Of Dti Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for one continued. article 7) (which showed low ADC), 9 articles [9][10][11]13,15,16,22,23,29) described high ADC in involved nerves and 5 articles demonstrated findings of ADC in healthy subjects 8,18,[24][25][26] . In an asymptomatic case, FA increased and ADC decreased following compression of the nerve root without injury 21) .…”
Section: Measurement Of Dti Parametersmentioning
confidence: 99%
“…7 post mortem subjects were investigated in one article 8) . 201 healthy volunteers were also investigated in 15 articles 8,11,14,[16][17][18][19][22][23][24][25][26][28][29][30] .…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 99%
“…Derived parameters from DWN or DTN, such as ADC or FA, have proved its usefulness to identify the involved lumbar nerve roots in cases of lumbar pain (57,58). An increase in ADC and a significant decrease in FA of compressed nerve roots compared with contralateral ones are detected in cases of symptomatic lumbar disk disease.…”
Section: A B D Cmentioning
confidence: 99%
“…Recently, the diffusion tensor imaging technique has been used for the structural and functional diagnosis of lumbar nerve damage before and after surgery. [19][20][21][22][23] Regarding surgical procedures, Cho et al [24] demonstrated that their floating technique reduces complications during PELD. In their series of 154 patients, none had ENR injury.…”
Section: Enr Injurymentioning
confidence: 99%